INCLUSIVE LEADERSHIP AND EMPLOYEE ENGAGEMENT: THE MEDIATING ROLE OF PSYCHOLOGICAL SAFETY AND ORGANIZATIONAL COMMITMENT: A LITERATURE REVIEW - Faizah, Lumatul; Juhdi, Nurita; Mustaffa, Nur Fariza (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Employee engagement is a critical factor influencing organizational performance, innovation, and retention in contemporary work environments. Leadership plays an essential role in shaping employee engagement; however, the mechanisms through which leadership affects engagement remain insufficiently integrated. This study aims to examine how inclusive leadership influences employee engagement through the mediating roles of psychological safety and organizational commitment. Using a literature review approach, this study synthesizes prior empirical and conceptual research on leadership and employee engagement. The findings indicate that inclusive leadership characterized by ethical behavior, openness, authenticity, and support enhances employee engagement both directly and indirectly. Psychological safety enables employee voice, trust, and participation, while organizational commitment strengthens employees’ emotional attachment and loyalty, translating supportive leadership practices into sustained engagement. This study concludes that employee engagement is most effectively fostered when inclusive leadership simultaneously cultivates psychologically safe work environments and strengthens organizational commitment, offering theoretical and practical insights for sustaining employee engagement.